2012
DOI: 10.1094/phyto-02-12-0023-rvw
|View full text |Cite
|
Sign up to set email alerts
|

Ilarviruses ofPrunusspp.: A Continued Concern for Fruit Trees

Abstract: Prunus spp. are affected by a large number of viruses, causing significant economic losses through either direct or indirect damage, which results in reduced yield and fruit quality. Among these viruses, members of the genus Ilarvirus (isometric labile ringspot viruses) occupy a significant position due to their distribution worldwide. Although symptoms caused by these types of viruses were reported early in the last century, their molecular characterization was not achieved until the 1990s, much later than fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 136 publications
4
101
1
2
Order By: Relevance
“…The present survey has shown that the level of Ilarvirus infections in stone fruit trees in mid hill zone of Himachal Pradesh is lower than that reported from other parts of the world (DiTerlizzi et al, 1992;Aouane, 2003;Polak, 2007;Matic et al, 2008;Scott 2014;Pallas et al, 2012) (Fig. 1-8).…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…The present survey has shown that the level of Ilarvirus infections in stone fruit trees in mid hill zone of Himachal Pradesh is lower than that reported from other parts of the world (DiTerlizzi et al, 1992;Aouane, 2003;Polak, 2007;Matic et al, 2008;Scott 2014;Pallas et al, 2012) (Fig. 1-8).…”
Section: Resultscontrasting
confidence: 46%
“…Prunus necrotic ringspot virus (PNRSV) and apple mosaic virus (ApMV) are common and widespread in different stone fruits causing crop losses (Scott, 2014;Pallas et al, 2012). In India, little is known on virus diseases of stone fruit trees and records are limited on the occasional finding of ilarviruses (PNRSV and ApMV) in major stone fruits grown in India (Kapoor and Handa, 2017a;Chandel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Scott (2018) studied the effect of prunus necrotic ring spot virus on growth, yield and quality of peach and found a reduction in tree growth between 12 to 70 percent and yield loss of 5 to 70 percent with fruits having lower soluble sugar content. PNRSV has also been reported to cause significant crop losses depending on the host (15 percent yield loss in sweet cherry and up to 100 percent in peach) and can reduce bud-take in nurseries, decrease growth of fruit from 10 to 30 percent and fruit yield reduction from 20 to 60 percent with delayed fruit maturity (Pallas et al, 2012).…”
Section: Geographical Distribution and Economic Importancementioning
confidence: 99%
“…Incidence of PNRSV was reported to be 60 percent in Georgia (Wells et al,1986); 25 percent in Turkey (Gumus et al, 2007); 70 and 100 percent in South Carolina (Scott 2014); 30 percent in Canada (Pallas et al, 2012); 25 percent in Mexico (Almaraz 2008); 32 percent in Saudi Arabia (Alhudaib and Rezk 2011); 15 percent in Central Bohemia, Czech Republic (Winkowska et al, 2016) and 18 percent in India (Kapoor and Handa 2017a Orchard-5 Jaunaji 10…”
Section: Data Presented Inmentioning
confidence: 99%